Standing repair of a proximal, incomplete, articular fracture of the third metatarsal bone. (1st June 2018) - Cillán‐García, E.; Reardon, R. J. M.; Schiavo, S.; Fordham, T.; Elce, Y. A.
Summary: A 5‐year‐old National Hunt Thoroughbred mare presented with sudden onset left hindlimb lameness after race training on the gallops. Clinical examination revealed a marked painful reaction over the proximal metatarsal region but no other obvious abnormalities were detected. Survey radiographs at the yard did not reveal any abnormalities. Nuclear scintigraphic examination 3 days after injury revealed focal marked increased radiopharmaceutical uptake in the proximal metatarsal region. Subsequent radiography revealed an incomplete, articular fracture of the proximal left third metatarsal bone. Repair of the fracture using 3 × 4.5 mm cortical screws placed in lag fashion was performed under standing sedation following perineural analgesia. Follow‐up radiographs demonstrated progressive healing of the fracture. The mare returned to race training 8 months after the fracture was repaired and raced successfully 12 months post injury.